Transboundary water interaction I: reconsidering conflict and cooperation - Zeitoun, Mark; Mirumachi, Naho (International environmental agreements : politics, law and economics, 2008)
Whether the inter-state and sub-national tensions over transboundary waters will lead to greater conflict or increased cooperation remains a hotly debated issue. Most work on the subject situates transboundary water conflict and transboundary water cooperation at opposing ends of a continuum. The examination of either conflict or cooperation, we argue, refutes the reality of the vast majority of contexts where cooperation and conflict actually co-exist, and perpetuates the paradigm that any conflict is ‘bad’, and that all forms of cooperation are ‘good’. The efforts of the international water academic and practitioner communities may be better served through a combined reading of conflict and cooperation as transboundary water interaction . Mirumachi’s Transboundary Waters Interaction NexuS is offered as a robust method demonstrating that simultaneous consideration of conflict and cooperation is both insightful and possible. Transboundary water interaction is shown to be an inherently political process determined by the broader political context. We examine evidence suggesting that uncritical acceptance of traditional forms of ‘cooperative’ arrangements may in fact sustain the conflict it was intended to transform. Several other less well-known faces of ‘cooperation’ are discussed in detail, with examples of narrow, token and coercive cooperation derived from inter-state relations on the Jordan, Nile and Ganges rivers. With a view to paving the way for improved transboundary water sharing and governance, subjectively negative, neutral and positive forms of interaction are defined, and linked with a first approximation of their potential driving forces.